Pengaruh Sistem Informasi Akuntansi (Komputerisasi Kegiatan Pertanahan) Terhadap Pencatatan Penerimaan Negara Bukan Pajak Pada Kantor Pertanahan Kabupaten Bengkalis - Dewi Angraini; Decky Hendarsyah (LPPM ISNJ Bengkalis, 2019)
This study was conducted to determine the effect of Accounting Information Systems (Computerization of Land Activities) on the Registration of Records of Non-Tax State Revenues according to Government Regulation Number 128 of 2015. This research was conducted at the Land Office of Bengkalis Regency. Data collection was done by giving questionnaires as much as 30 copies, which were distributed to respondents who are civil servants and non-permanent employees at the Bengkalis land office using Purposive Sampling. The data obtained were then analyzed using SPSS version 23.0. The test results show that the Accounting Information System (computerization of land activities) has a positive and significant effect on the recording of non-tax state revenue at the Bengkalis Regency land office. The contribution of the independent variable to the dependent variable is 25.3% while the rest 74.7% is influenced by other variables.